2014
DOI: 10.1093/treephys/tpu096
|View full text |Cite
|
Sign up to set email alerts
|

Uniform climate sensitivity in tree-ring stable isotopes across species and sites in a mid-latitude temperate forest

Abstract: Destroy this report when no longer needed. Do not return it to the originator. The findings in this report are not to be construed as an official Department of the Army position unless so designated by other authorized documents. The citation in this report of trade names of commercially available products does not constitute official endorsement or approval of the use of such products. REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188 PuMk; reporting bun^ for this coaacSon or ManroUon is estimated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 61 publications
7
56
0
Order By: Relevance
“…Similarly, Coulibaly et al [41] has reported that tree species with deep rooting systems are less vulnerable to water deficits. These results can be attributed to the fact that during extreme drought conditions, deep rooted saplings take advantage of their access to deeper soil horizons, which could result in increased photosynthetic activity and continued biomass production, as reported by Hartl-Meier et al [22] for beech (Fagus sylvatica L.) and larch (Larix decidua Mill.) under a temperate climate.…”
Section: Effects Of Rooting Depth On Biomass Growth Under Extreme Drysupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, Coulibaly et al [41] has reported that tree species with deep rooting systems are less vulnerable to water deficits. These results can be attributed to the fact that during extreme drought conditions, deep rooted saplings take advantage of their access to deeper soil horizons, which could result in increased photosynthetic activity and continued biomass production, as reported by Hartl-Meier et al [22] for beech (Fagus sylvatica L.) and larch (Larix decidua Mill.) under a temperate climate.…”
Section: Effects Of Rooting Depth On Biomass Growth Under Extreme Drysupporting
confidence: 55%
“…This observation suggests that drought vulnerability may be related to trees' ability to develop sufficiently deep root systems [21]. Hartl-Meier et al [22] found that among three tree species growing under similar temperate climate conditions, those with deep root systems benefited from the access to deep soil water, as reflected in their higher photosynthetic activity and continued biomass production during severe drought conditions. Therefore, the consideration of root systems in the analysis of climate-growth relationships may give new insights on species' responses to extreme climate events.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen isotopes in tree rings (δ 18 O TR ) are increasingly used as indicators of past climatic changes in temperate areas (Cernusak and English, 2015;Hartl-Meier et al, 2014;Saurer et al, 2008). They have been widely used to reconstruct past atmospheric conditions such as air temperature (Naulier et al, 2015), drought (Labuhn et al, 2016), precipitation amount (Rinne et al, 2013), isotopic composition of precipitation (Danis et al, 2006), relative air humidity (Wernicke et al, 2015), cloud cover (Shi et al, 2012), and even atmospheric circulation patterns (Brienen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of trees to record additional climate elements including relative humidity, sunshine and cloud cover changes has not been fully explored, and the combination of widely used TRW and MXD chronologies with other tree-ring proxies such as stable isotope ratios, height increments and cell parameters might further improve climate reconstructions (e.g., Bräun-ing, 2001;Carrer et al, 2016;Fonti & Babushkina, 2016;McCarroll et al, 2003). Only few studies have been conducted evaluating the climatic information recorded in both the classical tree-ring growth proxies, TRW and MXD, together with the stable isotope ratios, δ 13 C and δ 18 O (e.g., Esper et al, 2015a;Gagen et al, 2006;Hartl-Meier et al, 2015;Kirdyanov et al, 2008;Treydte et al, 2001).…”
Section: Introductionmentioning
confidence: 99%